2021
DOI: 10.1007/s40279-021-01516-8
|View full text |Cite|
|
Sign up to set email alerts
|

Through the Looking Glass: A Systematic Review of Longitudinal Evidence, Providing New Insight for Motor Competence and Health

Abstract: Introduction In 2008, a conceptual model explaining the role of motor competence (MC) in children’s physical activity (PA), weight status, perceived MC and health-related fitness was published. Objective The purpose of the current review was to systematically compile mediation, longitudinal and experimental evidence in support of this conceptual model. Methods This systematic review (registered with PROSPERO on 28 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
218
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(241 citation statements)
references
References 89 publications
(473 reference statements)
16
218
2
5
Order By: Relevance
“…Whilst the review found strong evidence for a negative association between FMS and weight status in both directions, there was indeterminate evidence for a pathway from FMS to PA and no evidence for the reverse pathway. Although there were findings of a bidirectional longitudinal associations between FMS competency and weight status, consistent with the Stodden, Goodway [ 2 ] model, the review authors recommended that further robust longitudinal and experimental studies examining changes in FMS relative to change in other constructs are needed [ 14 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whilst the review found strong evidence for a negative association between FMS and weight status in both directions, there was indeterminate evidence for a pathway from FMS to PA and no evidence for the reverse pathway. Although there were findings of a bidirectional longitudinal associations between FMS competency and weight status, consistent with the Stodden, Goodway [ 2 ] model, the review authors recommended that further robust longitudinal and experimental studies examining changes in FMS relative to change in other constructs are needed [ 14 ].…”
Section: Introductionmentioning
confidence: 93%
“…As such, further longitudinal studies are needed to examine the developmental trajectory of FMS competence with PA and obesity as proposed in the Stodden, Goodway [ 2 ] model. A recent systematic review by Barnett, Webster [ 14 ] looked to compile evidence from mediation, longitudinal and experimental studies in support of the Stodden, Goodway [ 2 ] model. Whilst the review found strong evidence for a negative association between FMS and weight status in both directions, there was indeterminate evidence for a pathway from FMS to PA and no evidence for the reverse pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, children's tendency to overestimate their actual motor competence (AMC) is considered to be a positive motivator for increasing physical activity (PA) (Stodden et al, 2008;Robinson et al, 2015). Due to the inflated PMC of children, the relationship between PMC and AMC is not expected to correlate (Lopes et al, 2016;Hall et al, 2019;Lopes et al, 2018;True et al, 2017;Barnett et al, 2021). Yet, not all young children have inflated PMC (Robinson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The amelioration of overall motor skill competence in the enriched PE group and its worsening in the traditional PE group over the intervention time (Figure 3) confirms that at the threshold to adolescence, designed specialist-led interventions have the potential to promote motor skill competence [7,8] and even prevent its deterioration. The relevance of interventions that aid motor competence development in preadolescence is especially evident when considering the predictive role of overall motor competence in childhood for later PA levels [4,82,83] and, conversely, the worldwide high rates of insufficient PA in adolescence [84]. Reviews of interventions targeted to motor competence [8,85] called for attention to the theoretical or pedagogical approaches to gain a better understanding of the features of efficacious interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention to PE outcomes in the motor domain has been attracted by the flourishing of research on the development of motor competence-that is the ability to perform goal-directed movements-and its predictive value for positive trajectories of physical health [3,4] and cognitive development [5]. Curriculum-based PE shows, metaanalytically, a significant beneficial effect on overall motor competence in children and adolescents regardless of age and amount of PE time [6].…”
Section: Introductionmentioning
confidence: 99%